2005
DOI: 10.1021/bi048296z
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Newly Synthesized Sterol to the Sterol-Enriched Plasma Membrane Occurs via Nonvesicular Equilibration

Abstract: The mechanism by which newly synthesized sterols are transported from their site of synthesis, the endoplasmic reticulum (ER), to the sterol-enriched plasma membrane (PM) is not fully understood. Studies in mammalian cells suggest that newly synthesized cholesterol is transported to the PM in Golgi-bypassing vesicles and/or via a nonvesicular process. Using the yeast Saccharomyces cerevisiae as a model system, we now rule out an essential role for known vesicular transport pathways in transporting the major ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
188
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(218 citation statements)
references
References 51 publications
18
188
3
Order By: Relevance
“…Both vesicular and nonvesicular lipid transport mediate intracellular lipid trafficking from the ER. Yet, inhibition of vesicular transport by pharmacological and genetic manipulations such as BFA or colchicine treatment, ATP depletion, and specific sec mutants (such as Sec18 mutant) has no effect on intracellular transport of certain lipid species (Kaplan and Simoni 1985b;Urbani and Simoni 1990;Heino et al 2000;Baumann et al 2005). Furthermore, imaging and biochemical studies using fluorescent lipid analogs, such as DHE (dehydroergosterol; a fluorescent cholesterol analog) and radioactive labels lipids, respectively, support the involvement of nonvesicular transport in intracellular lipid trafficking (Maxfield and Mondal 2006).…”
Section: Nonvesicular Lipid Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Both vesicular and nonvesicular lipid transport mediate intracellular lipid trafficking from the ER. Yet, inhibition of vesicular transport by pharmacological and genetic manipulations such as BFA or colchicine treatment, ATP depletion, and specific sec mutants (such as Sec18 mutant) has no effect on intracellular transport of certain lipid species (Kaplan and Simoni 1985b;Urbani and Simoni 1990;Heino et al 2000;Baumann et al 2005). Furthermore, imaging and biochemical studies using fluorescent lipid analogs, such as DHE (dehydroergosterol; a fluorescent cholesterol analog) and radioactive labels lipids, respectively, support the involvement of nonvesicular transport in intracellular lipid trafficking (Maxfield and Mondal 2006).…”
Section: Nonvesicular Lipid Transportmentioning
confidence: 99%
“…The transport of sterols from the ER is unaffected by drugs or genetic mutations that block vesicular transport, and is thought to be mediated mainly by spontaneous lipid transfer and by certain LTPs (Urbani and Simoni 1990;Heino et al 2000;Maxfield and Wustner 2002;Baumann et al 2005). Although sterols are highly hydrophobic lipids their spontaneous movement between certain membranes could be very rapid (a half-time of 1 min or less) (Dawidowicz 1987), and can thereby support substantial sterol transport between specific membranes.…”
Section: Lipid Transport From the Ermentioning
confidence: 99%
“…Previous studies have identified the PM-associated ER as sites of phosphatidylinositol (PI) metabolism, nonvesicular transfer of sterols, and Ca 2þ level regulation (Li and Prinz 2004;Baumann et al 2005;Carrasco and Meyer 2011;Stefan et al 2011). EM analysis has revealed that 20% -45% of the cytoplasmic surface of the PM in budding yeast is within tethering distance of the ER and ribosome excluded (Fig.…”
Section: Er and Plasma Membranementioning
confidence: 99%
“…Previous studies have shown that cholesterol and related sterols move by vesicular and non-vesicular pathways between the plasma membrane and intracellular compartments (Baumann et al 2005;Hao et al 2002;Kaplan and Simoni 1985;Li and Prinz 2004;Wüstner et al 2002). Employing the intrinsically fluorescent sterol dehydroergosterol (DHE), it was shown that the endocytic recycling compartment (ERC) is a major sterol storage compartment under basal conditions in non-polarized cells including macrophages Wüstner et al 2005).…”
Section: Introductionmentioning
confidence: 99%